Cover Feature: New Kids in Lactide Polymerization: Highly Active and Robust Iron Guanidine Complexes as Superior Catalysts (ChemSusChem 10/2019). Issue 10 (13th May 2019) - Rittinghaus, Ruth D.; Schäfer, Pascal M.; Albrecht, Pascal; Conrads, Christian; Hoffmann, Alexander; Ksiazkiewicz, Agnieszka N.; Bienemann, Olga; Pich, Andrij; Herres‐Pawlis, Sonja
Abstract : The Cover Feature shows iron guanidine complexes as applied for ring‐opening polymerization of lactide, with tin(II)octanoate [Sn(Oct2 )] in the background. This research demonstrates, for the first time, a biocompatible complex which can surpass Sn(Oct)2 in its polymerization activity under industrially relevant conditions. More information can be found in the Communication by Rittinghaus et al. on page 2161 in Issue 10, 2019 (DOI: 10.1002/cssc.201900481 ).